Simultaneous removal of ternary heavy metal ions by a newly isolated Microbacterium paraoxydans strain VSVM IIT(BHU) from coal washery effluent - Singh V.; Singh J.; Singh N.; Rai S.N.; Verma M.K.; Verma M.; Singh V.; Chivate M.S.; Bilal M.; Mishra V. (My University, 2025)
In the present work, the removal of Cr (VI), Cd (II) and Pb (II) at 50 mg/L of each metal ion concentration was investigated by Microbacterium paraoxydans strain VSVM IIT(BHU). The heavy metal binding on the bacterial cell surface was confirmed through X-ray photoelectron spectroscopy and energy dispersive X-ray. X-ray photoelectron spectroscopy analysis also confirmed the reduction of Cr (VI) to Cr (III). Heavy metal removal dynamics was investigated by evaluating dimensionless, and the value of Nk (9.49 × 10–3, 9.92 × 10–3 and 1.23 × 10–2 for Cr (VI), Cd (II) and Pb (II) ions) indicated that the removal of heavy metals by bacterial isolate was mixed diffusion and transfer controlled. It was found that both the experimental and predicted values for isolated bacterial strain coincided with each other with a good R2 value in the L-M Algorithm range of 0.94–0.98 for the ternary metal ion system. The bacterial isolate presented a maximum heavy metal ion removal efficiency of 91.62% Cr (VI), 89.29% Pb (II), and 83.29% Cd (II) at 50 mg/L. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.